(untitled) (Community Based Medical Journal, 2015)
Leprosy caused by Mycobacterium leprae, is still considered a major health problem in many developing countries. The routine bacteriological test on the demonstration of acid-fast bacilli in skin smears is not sufficiently sensitive or specific in the paucibacillary leprosy patients. To detect DNA of Mycobacterium leprae by Polymerase Chain Reaction (PCR) from skin biopsy specimen as a means of diagnosis of paucibacillary leprosy. It was a cross-sectional study of clinically diagnosed 33 cases of Paucibacillary leprosy patients. Laboratory works were performed in the Department of Microbiology and Immunology and Department of pathology; Bangabandhu Sheikh Mujib Medical University (BSMMU) and Leprosy Control Institute and Hospital, Mohakhali, Dhaka from November 2013 to June 2015. It was observed that the mean age of patients was found 30.9±13.7 years, 19(57.6%) patients had two to five skin lesions, all (100%) patients had tuberculoid type of leprosy, all (100%) patients had loss of sensation and 18(54.5%) patients had nerve thickening. Regarding slit skin smear test, it was observed that all (100%) patients were slit skin smear negative for leprosy bacilli, 8(24.2%) patients had positive skin biopsy for histopathology and 15(45.5%) patients had positive skin biopsy for PCR. The validity of PCR for identification of paucibacillary leprosy correlated with sensitivity 100%, specificity 72%, accuracy 78.8%, positive predictive value 53.3% and negative predictive value 100%. Polymerase chain reaction (PCR) has definite value in the diagnosis of paucibacillary leprosy and can be regarded as a sensitive and specific diagnostic modality. CBMJ 2015 July: Vol. 04 No. 02 P: 41-48